Majorization for Certain Classes of Analytic Functions Defined by Fournier–Ruscheweyh Integral Operator - Murli Manohar Gour; Pranay Goswami; Basem Aref Frasin; Saad Althobaiti (Journal of Mathematics)
In this paper, we introduce three new classes SkaM,N;μ,Rkaμ, and Tkaθ of analytic functions defined by Fournier–Ruscheweyh integral operator. For these classes, we investigate the majorization problem. Furthermore, a number of new results are shown to follow upon specializing the parameters involved in our main results.